2021
DOI: 10.3390/ijms22094409
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of High-Grade Serous Carcinogenesis in the Fallopian Tube and Ovary: Current Hypotheses, Etiologic Factors, and Molecular Alterations

Abstract: Ovarian high-grade serous carcinomas (HGSCs) are a heterogeneous group of diseases. They include fallopian-tube-epithelium (FTE)-derived and ovarian-surface-epithelium (OSE)-derived tumors. The risk/protective factors suggest that the etiology of HGSCs is multifactorial. Inflammation caused by ovulation and retrograde bleeding may play a major role. HGSCs are among the most genetically altered cancers, and TP53 mutations are ubiquitous. Key driving events other than TP53 mutations include homologous recombinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 139 publications
0
15
0
Order By: Relevance
“…Using CHIP-seq and transcriptomic studies, Lawrensen et al found that the transcription factor SOX18, which was overexpressed in tumors, induced an EMT in FTEs from patients with HGSC [21], suggesting that an EMT in FTE may represent an early molecular mechanism of HGSC development. In addition to EMT, many other genetic changes are found within the FTE of BRCA mutation carriers [22,23]. Many previous studies addressing BRCA germline mutation-associated etiologies are bulk sequencing or tissue based, and therefore unable to identify subpopulations within the FTE since all cells derived from FTE were evaluated together as a single sample.…”
Section: Introductionmentioning
confidence: 99%
“…Using CHIP-seq and transcriptomic studies, Lawrensen et al found that the transcription factor SOX18, which was overexpressed in tumors, induced an EMT in FTEs from patients with HGSC [21], suggesting that an EMT in FTE may represent an early molecular mechanism of HGSC development. In addition to EMT, many other genetic changes are found within the FTE of BRCA mutation carriers [22,23]. Many previous studies addressing BRCA germline mutation-associated etiologies are bulk sequencing or tissue based, and therefore unable to identify subpopulations within the FTE since all cells derived from FTE were evaluated together as a single sample.…”
Section: Introductionmentioning
confidence: 99%
“…They have also demonstrated genomic alterations in the homologous recombination repair (HRR) pathway leading to genomic instability and aneuploidy characterised by high copy number structural alterations (CNAs). CNAs can be recognised as oncogene amplifications such as CCNE1 (20%), MECOM, EMSY and MYC and deletions/breaks of tumour suppressor genes such as PTEN, RB1, RAD51B and NF1 [38,39]. Additionally, recurrent mutations have been observed in a variety of genes such as NF1 (4%-6%), RB1 (2%-6%)and PTEN (<1%) along with structural alterations/deletions can result in genes inactivation in relatively high frequency such as 20%, 17% and 7%, respectively [38,40].…”
Section: Molecular Pathology Of Ovarian High-grade Serous Carcinomasmentioning
confidence: 99%
“…Indeed, both germline and somatic deleterious mutations in BRCA1/2 genes (referred to as gBRCA* and sBRCA* , respectively) have been shown to promote HGSOC [ 9 , 24 ]. BRCA1/2 play key roles in genome integrity maintenance and their alteration are an early event in the EOC carcinogenetic process; indeed, the loss of the first allele of BRCA1 (or BRCA2 ) is a facilitating event for TP53 loss, both of them leading to EOC development [ 25 ]. The most frequent and well-known alterations are short mutations in BRCA1/2 genes, leading to coding sequence disruption (through missense, nonsense or frameshift mutations) that subsequently inactivate proteins or result in dominant-negative mutations [ 26 ].…”
Section: From Ovarian Cancer Genetics To Homologous Recombination Def...mentioning
confidence: 99%